Mutually Orthogonal Golay Complementary Sequences in Synthetic Aperture Imaging Systems - Ihor TROTS (Archives of Acoustics, 2015)
The main objective of this study is to improve the ultrasound image by employing a new algorithm based on transducer array element beam pattern correction implemented in the synthetic transmit aperture (STA) method combined with emission of mutually orthogonal complementary Golay sequences. Orthogonal Golay sequences can be transmitted and received by different transducer elements simultaneously, thereby decreasing the time of image reconstruction, which plays an important role in medical diagnostic imaging.